Monkeypox - review - Aleksandra Amalia Kuchnicka; Katarzyna Kosz; Julia Kuchnicka; Klaudia Remjasz; Natalia Zarankiewicz; Martyna Zielińska; Klaudia Sapuła; Jakub Aleksandrowicz; Wojciech Siedlecki (Journal of Education, Health and Sport, 2022)
Introduction and purpose: